2018
DOI: 10.1016/j.jbi.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Auditing SNOMED CT hierarchical relations based on lexical features of concepts in non-lattice subgraphs

Abstract: Our results demonstrate that analyzing the lexical features of concepts in non-lattice subgraphs is an effective approach for auditing SNOMED CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…These aspects are usually modelled by calculating different hierarchical-based features, where higher values of depth and breadth variance in the class hierarchy tree are associated with better semantic relations [ 19 , 39 ]. Our solution is in line with [ 44 , 45 ], which proposed a lexical study in order to discover the possible inconsistencies. [ 44 ] focused on the semantics of sets that group lexically similar concepts, and [ 45 ] used subgraphs enriched with lexical characteristics obtained along the is-a relationships.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These aspects are usually modelled by calculating different hierarchical-based features, where higher values of depth and breadth variance in the class hierarchy tree are associated with better semantic relations [ 19 , 39 ]. Our solution is in line with [ 44 , 45 ], which proposed a lexical study in order to discover the possible inconsistencies. [ 44 ] focused on the semantics of sets that group lexically similar concepts, and [ 45 ] used subgraphs enriched with lexical characteristics obtained along the is-a relationships.…”
Section: Discussionmentioning
confidence: 62%
“…Our solution is in line with [ 44 , 45 ], which proposed a lexical study in order to discover the possible inconsistencies. [ 44 ] focused on the semantics of sets that group lexically similar concepts, and [ 45 ] used subgraphs enriched with lexical characteristics obtained along the is-a relationships. The approach followed in our work was to focus on the LR classes, which are classes whose label is a lexical regularity.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Liu et al created embeddings for each concept based on its related IS-A relations and used convolutional neural network to discover missing IS-A relations between neoplasm concepts in the NCI Thesaurus [13]. In our previous works [14][15][16][17][18][19][20], we found that non-lattice subgraphs often reveal quality issues including missing IS-A relations. For instance, lexical-based approaches based on non-lattice subgraphs were developed to identify missing IS-A relations in the SNOMED CT [17,18] and NCI Thesaurus [19,20].…”
Section: Related Work On Identifying Missing Is-a Relationsmentioning
confidence: 90%
“…This method used 4 patterns to cover about 4% of all non-lattice fragments in SNOMED CT, with a solid precision rate (59%) of confirmed errors by domain experts. More recently, a new structural-lexical approach leveraged more existing knowledge in SNOMED CT by enriching the lexical attributes of each concept in non-lattice subgraphs to facilitate the identification of missing is-a relations [17]. This approach covered 7.4% of non-lattice subgraphs with higher precision (82.96%).…”
Section: Discussionmentioning
confidence: 99%